Karawitan Bali Dalam Perspektif Rasa - I Wayan Suweca (Mudra Jurnal Seni Budaya, 2007)
This article is written in order to make a deeply understanding about the concept of Balinese traditional music, especially which related with the sense of musical. The aim of this article is to observe some theories which can be used by the composer in creating songs with sense and different variations of musical. With detail observation of many kind elements that has the possibility to influence and take a part in conveying sense. The method used is the compotation of the composer from some decade. With the priority of the critical science of the study as the main problem in the method used, and hopefully the resume can be used in fixing the study tools about Balinese traditional music. By the understanding of the musical sense as one part of the concept in creating the scientific Balinese traditional music, will open the nest generation ways in thinking to act and create something regularly.